Does Combined Osteopenia/Osteoporosis and Sarcopenia Confer Greater Risk of Falls and Fracture Than Either Condition Alone in Older Men? The Concord Health and Ageing in Men Project. (18th July 2018) - Scott, David; Seibel, Markus; Cumming, Robert; Naganathan, Vasi; Blyth, Fiona; Le Couteur, David G; Handelsman, David J; Waite, Louise M; Hirani, Vasant
Abstract: Background: It is unclear whether older men with osteopenia/osteoporosis and sarcopenia (so-called osteosarcopenia) are at greater risk of falls and fractures than those with either condition alone. Methods: One thousand five hundred seventy-five community-dwelling men aged ≥70 years had appendicular lean mass, total hip and lumbar spine bone mineral density determined by dual-energy x-ray absorptiometry, and completed hand grip strength and gait speed tests. Osteopenia/osteoporosis was defined as a T-score at any site ≤−1.0 SD . Sarcopenia was defined using the European Working Group on Sarcopenia algorithm. Participants were contacted every 4 months for 6 ± 2 years to ascertain incident fractures (confirmed by radiographic reports) and for 2 years for incident falls. Results: Prevalence of osteosarcopenia was 8%, while 34% of participants had osteopenia/osteoporosis alone and 7% had sarcopenia alone. Men with osteosarcopenia had significantly increased fall (incidence rate ratio: 1.41; 95% confidence interval [CI]: 1.02 to 1.95) and fracture risk (hazard ratio: 1.87; 95% CI: 1.07 to 3.26) compared with men with neither osteopenia/osteoporosis nor sarcopenia. There was no statistical interaction between osteopenia/osteoporosis and sarcopenia, and falls and fracture risk were not different for osteosarcopenia compared with either condition alone (all p > .05). Conclusions: Community-dwelling older men with combined osteopenia/osteoporosis and sarcopenia do not have increased falls and fracture risk compared with those with either condition. Further research is required to clarify whether the term "osteosarcopenia" has any meaning above and beyond either term alone and therefore potential clinical utility for falls and fracture prediction.